Analysis of Land Cover Change in Relation to the Urban Heat Island Phenomenon using Remote Sensing and GIS Technology in South Jakarta, Indonesia - Whidayanti, Ella; Labib, Muhammad Syauqi; Novani, Nabilah Rizki; Hazani, Syahla Nuzla; Akyas, Muhammad (Journal of Geographical Sciences and Education, 2025)
The Urban Heat Island (UHI) phenomenon is one of the most significant environmental impacts resulting from land cover changes in urban areas. This study aims to analyze the relationship between land cover change and the UHI phenomenon in South Jakarta through the use of remote sensing and Geographic Information System (GIS) technologies. The data used comprise Landsat-8 OLI/TIRS from 2015 to 2018 to generate NDVI, NDWI, NDBI, Land Cover, and Land Surface Temperature (LST) indices. Pearson correlation test was also conducted to determine the variables that most influence the UHI phenomenon. The land cover changes, particularly the expansion of built-up areas and the reduction of vegetation—directly contribute to an increase in surface temperature. The correlation analysis reveals that NDBI consistently exerts the strongest influence on UHI (0.55), followed by NDWI (0.21) and NDVI (0.18). This research underscores the critical importance of land-use regulation as a strategic approach to mitigating UHI in urban environments.